2021
DOI: 10.15587/1729-4061.2021.245360
|View full text |Cite
|
Sign up to set email alerts
|

Improved performance of corrugated metal gaskets in boiler’s piping system through multilayered coating

Abstract: The corrugated metal gasket is still in the early stages of development. However, gasket contact flanges with a high surface roughness (more than 3.5 µm) leak and require a lot of force to tighten. A nickel or copper-coated corrugated metal gasket was designed. A water pressure test was used to measure leaks, and the results revealed that nickel or copper-covered gaskets performed better. The effect of high temperature has not been explored in this study, which only reveals high pressure. The goal of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…A nickel strike is carried out for 30 minutes so that the brass plating can be done. At this stage, the electrolyte solution used contains nickel sulfate (NiSO 4 ) with a composition of 240 g/L, nickel chloride (NiCl 2 ) with a composition of 55 g/L, (H 3 BO 3 ) with a composition of 55 g/L and a pH of 4 [14]. The last step is the process of coating the joints using brass metal.…”
Section: Electroplating Processmentioning
confidence: 99%
“…A nickel strike is carried out for 30 minutes so that the brass plating can be done. At this stage, the electrolyte solution used contains nickel sulfate (NiSO 4 ) with a composition of 240 g/L, nickel chloride (NiCl 2 ) with a composition of 55 g/L, (H 3 BO 3 ) with a composition of 55 g/L and a pH of 4 [14]. The last step is the process of coating the joints using brass metal.…”
Section: Electroplating Processmentioning
confidence: 99%
“…The earlier study [10] looked at CMGs that had been electroplated with nickel and copper once more. The outcomes demonstrated that, when assessed at high pressure, gaskets function effectively and sealed pipe joints leak pro perly.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The dies used have been made with dimensions determined as in previous studies [10]. The Taguchi and finite element approaches' optimal dimensioning techniques were used to calculate the die dimensions.…”
Section: Forming Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The condition of the contact surface between the flange and the gasket influences the sealing performance of the gasket, which decreases as the smoothness of the contact surface decreases [17,18]. Efforts to improve gasket performance are carried out either by coating [19][20][21], laminating [22], or redesigning [23]. Based on this, in this study, let's try to improve the performance of the gasket from previous studies [17] by layering the outside with cooper which is also influenced by the surface roughness of the flange so that the performance of the three-layer gasket is indeed better than the previous gasket.…”
Section: Introductionmentioning
confidence: 99%